Microestrutura e propriedades elétricas de compósitos NiO/Ni-GDC para aplicação como anodo de célula a combustível de óxido sólido - Araújo, Allan Jedson Menezes de (2018)
The aim of this work was to study the electrical properties of NiO/Ni-Ce0.9Gd0.1O1.95 (NiO/Ni-GDC) composites, usually used as anode materials for Solid Oxide Fuel Cells. NiO-GDC composites were obtained by a one-step synthesis route which are characterized by simultaneously obtaining the NiO and GDC phases in a single polymeric precursor. A resulting resin was heat treated at 350 ºC and the precursor powder was calcined at 700 °C. The phase composition was varied according to the following proportions (by mass): 30:70, 40:60 and 50:50 (NiO/GDC). The obtained samples were characterized by X-ray diffractometry (XRD) and transmission electron microscopy (TEM). The powders were compacted by isostatic pressing at 200 MPa, sintered at 1450, 1500 and 1550 °C in air, and subsequently reduced to Ni-GDC under a hydrogen atmosphere. The apparent porosity of composites (NiO-GDC) and cermets (Ni-GDC) was evaluated using the Archimedes method and the response interpreted through the analysis of variance and response surface of a 2² factorial design with central point and replicate. The effects of the phase composition and the sintering temperature on the microstructure and electrical properties were investigated by scanning electron microscopy (SEM) and impedance spectroscopy (between 250 and 650 °C). The refinement of the XRD data indicated that the particulate materials have nanometric characteristics and the crystallite size of the GDC phase tends to decrease with increasing the NiO content. Archimedes analysis shows that samples of NiO-GDC composites are extremely dense (porosities below 0.54%) and those samples of Ni-GDC cermets have open porosity between 1.36 and 19.11%. From the experimental design it was possible to obtain a significant linear model (95% confidence level) for the porosity of the cermets according to the NiO content and sintering temperature. The electrical properties indicated that the composites with 50 wt.% NiO showed twice the conductivity of the composites with the lower content of NiO at temperatures above 500 ºC. The good electrical performance of Ni-GDC cermets (resistivity between 0.43 and 1.19 ohm.cm at 650 °C) compared to materials from literature is a result of a high contiguity of the metal phase.